Locating transport sector responsibilities for the wellbeing of mobility-challenged people in Aotearoa New Zealand - Meher M; Spray J; Wiles J; Anderson A; Willing E; Witten K; ‘Ofanoa M; Ameratunga S (Elsevier Ltd, 2021)
Introduction wellbeing is a central tenet in the Aotearoa New Zealand government's Transport Outcomes Framework. Yet considerations of how place mediates diverse opportunities for wellbeing seldom identify how decision-making on transport and pedestrian infrastructure affects these opportunities. Considering the lived realities of older people and people with disabilities with a specific focus on Indigenous people, we argue it is particularly important to identify the role infrastructure plays in enhancing or undermining wellbeing for diverse communities. We also highlight state or sector responsibility for neglectful, wellbeing-diminishing infrastructure. Methods we ground this argument in community-based participatory research findings of qualitative interviews conducted at home and during neighbourhood walks with 62 older or mobility impaired people in socio-demographically diverse neighbourhoods in Auckland, Aotearoa New Zealand. The interviews explore community perceptions of mobility and wellbeing as experienced through the losses, stresses and joys of everyday life contexts and places. Results we find that people seek experiences of beauty, joy, belonging, fitness, and sociality when going out, but the pursuit of these are curtailed by significant infrastructural impediments with attendant emotional costs, burdens, and risks. Historical decisions shape contemporary possibilities for wellbeing in place, and historical infrastructural injustices impacting on transport and mobility particularly affect Indigenous people's opportunities for mobility-based wellbeing. Conclusion drawing on place-specific history and experiences of risk, we shift focus from individualized capacities to live well to conceptualizing wellbeing at a collective level, exploring place-based possibilities for a good life. These elaborations allowed us to identify signs of policy and practice abandonment and neglect, and articulate a vision for more inclusive, equitable transport infrastructure that enables the wellbeing of people differently challenged by urban environments.
© 2021 The Authors